1998
DOI: 10.1099/0022-1317-79-6-1519
|View full text |Cite
|
Sign up to set email alerts
|

Role of the helper component in vector-specific transmission of potyviruses.

Abstract: Four aphid species were tested for their ability to transmit tobacco etch (TEV) and turnip mosaic (TuMV) potyviruses. Myzus persicae and Aphis gossypii transmitted both viruses efficiently from infected plants, whereas Lipaphis erysimi transmitted only TuMV and Myzus ascalonicus was a poor or non-transmitter of either virus. Similar electrically monitored probing patterns were produced by M. persicae, L. erysimi and M. ascalonicus, ruling out behavioural differences as the cause of differential transmission. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 21 publications
0
25
0
1
Order By: Relevance
“…Hence, identification of vectors for SPMMV will provide an interesting subject for study. One scenario could be that the HC-Pro of a co-infecting potyvirus facilitates aphid transmission of SPMMV from the host (Kassanis & Govier, 1971;Sako & Ogata, 1981;Wang et al, 1998). In East Africa, co-infections of SPMMV with the potyvirus SPFMV are up to 3-fold more common than infections with SPMMV alone in cultivated sweetpotatoes ( Table 4.…”
Section: Selection Pressure and Recombination In Ipomovirusmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, identification of vectors for SPMMV will provide an interesting subject for study. One scenario could be that the HC-Pro of a co-infecting potyvirus facilitates aphid transmission of SPMMV from the host (Kassanis & Govier, 1971;Sako & Ogata, 1981;Wang et al, 1998). In East Africa, co-infections of SPMMV with the potyvirus SPFMV are up to 3-fold more common than infections with SPMMV alone in cultivated sweetpotatoes ( Table 4.…”
Section: Selection Pressure and Recombination In Ipomovirusmentioning
confidence: 99%
“…HC-Pro is a suppressor of RNA silencing and considered to be an important determinant of virus-host interactions (Anandalakshmi et al, 1998;Brigneti et al, 1998;Kasschau & Carrington, 1998;Torres-Barceló et al, 2008;reviewed by Rajamäki et al, 2004). HC-Pro is also necessary for transmission of potyviruses by aphids (Govier & Kassanis, 1974;Blanc et al, 1998;Wang et al, 1998). The lack of HC-Pro in three ipomoviruses raises questions about the importance of this protein for SPMMV.…”
Section: Introductionmentioning
confidence: 99%
“…Within the plant host, infections are phloem-limited and the viruses are acquired and transmitted by their respective vectors only upon phloem feeding. Recent studies have provided important information regarding specific virus-vector interactions which facilitate the transmission of several plant viruses, including those having non-circulative non-persistent, T. Tian and others T. Tian and others (Klaassen et al, 1995 circulative non-propagative and circulative propagative transmission relationships (Schmidt et al, 1994 ;Bruyere et al, 1997 ;Hofer et al, 1997 ;Bandla et al, 1998 ;Wang et al, 1998 ;Kikkert et al, 1998). In all cases, virion capsid or membrane proteins are associated with vector-mediated virus transmission and for potyviruses and caulimoviruses, a second protein (the HC-Pro or ATF, respectively) is essential for transmission also.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is unclear if the interaction between HC-Pro and CP\virion observed for TVMV and ZMV (Blanc et al, 1997 ;Peng et al, 1998) is a general phenomenon for all potyviruses. Wang et al (1998) showed that HC-Pro can regulate aphid-transmission specificity, suggesting direct association of HC-Pro with aphid stylets. Nevertheless, potyviral HC-Pro itself might not interact directly with CP or virions in the aphid but simply mediate indirectly the binding of virus particles to the aphid by inducing a conformational change of the putative aphid receptor or modifying the chemical environment or charge in aphid mouthparts.…”
mentioning
confidence: 99%